Par-eikon: przypadek Ostatniej Wieczerzy - Zarychta, Anna (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2014)
The text is an attempt to analyze the evolution of aesthetic forms and motifs discussed on the example of the so-called “great figure” The Last Supper – the starting point for the analysis of the motif is the photography of David La Chapelle of the series: Jesus is my homeboy. Significant here is the context theory of parody by Linda Hutcheon – understood as a central point overview of contemporary art – a phenomenon combining fidelity to tradition and contemporary ideas of creative freedom, to express, among others, in need of confrontation with the ‘classic’ conventions – encroaching and deconstructive also in our contemporary pop-cultural processes of “image-consumption”.